Peculiarities of Judicial Control During Pre-Trial Investigation - Teremetskyi , Vladyslav I.; Bandurka , Serhii S.; Korniienko , Maksym V.; Dniprov, Oleksii S.; Slobodenіuk , Inna V.; Albul , Serhii V.; Riabchenko , Yurii Y. (Journal of Ecohumanism, 2024)
The research is devoted to the peculiarities of judicial control during pre-trial investigation with due regard to the existing regulatory provisions and scientific research on this issue. The authors of the article have revealed the prerequisites for exercising judicial control at the pre-trial investigation stage. The definition of judicial control during pre-trial investigation has been provided. Characteristic features of this type of judicial control have been singled out. The purpose of judicial control during pre-trial investigation has been determined. The relationship between the function of judicial control and the function of justice has been identified, taking into account the norms of the current legislation and scientific research on this issue. The content of judicial control at the stage of pre-trial investigation has been analyzed. The peculiarities of its implementation during secret investigative actions, arrest and detention of a person, as well as under martial law conditions have been considered in detail. The need to harmonize the legislative amendments defining the legal regime of judicial control during pre-trial investigation under martial law with the requirements of international standards in the field of protection of human rights and freedoms, with the aim of achieving a compromise between public and private interests, have been emphasized.